A Case Study of Culturing Children's Independence Attitude Through Parent’s Role and Teacher’s Role - Ratna Purwanti; Muhammad Saleh; Yusi Mardatila; Rahmat Alfian Madani (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2022)
In the family environment, parents play an important role in children development. Meanwhile at schools, teachers’ role is also vital in strengthening children’s character. The problem that should be addressed is that parents should cooperate with teachers in instilling good values, such as independence, in children. Independence prevents children from being dependent on others and the most important thing is cultivating children’s courage and motivation to continue exploring new knowledge. Independence encourages children to learn about behavioral choices and risks that must be accounted for. The purpose of this study was to describe the guidance of parents and teachers in instilling children's independence. This research was conducted using the qualitative method with a descriptive research approach. The research location was in At-Tibyan Kindergarten. The data were collected using observations, documentation, and interviews with the principal, teachers, parents, and children in group B. The results of the study found that parental guidance in instilling children's independence was done by providing children with good examples, giving choices to children, guiding children in solving problems, giving sincere praises to children, providing support to children, and developing good communication with them. Meanwhile, the teacher's guidance was conducted through habituation and by establishing harmonious relationships with children, providing a good understanding to children, providing clear information to children, giving advice to children, and assisting them in problem-solving. This research can be used as input in instilling children's independence through guidance at home and school.